TGF-β1 signaling plays a dominant role in the crosstalk between TGF-β1 and the aryl hydrocarbon receptor ligand in prostate epithelial cells - Staršíchová, Andrea; Hrubá, Eva; Slabáková, Eva; Pernicová, Zuzana; Procházková, Jiřina; Pěnčíková, Kateřina; Seda, Václav; Kabátková, Markéta; Vondráček, Jan; Kozubík, Alois; Machala, Miroslav; Souček, Karel (Cellular signalling, 2012)
Crosstalk between the aryl hydrocarbon receptor (AhR) and transforming growth factor-β1 (TGF-β1) signaling has been observed in various experimental models. However, both molecular mechanism underlying this crosstalk and tissue-specific context of this interaction are still only partially understood. In a model of human non-tumorigenic prostate epithelial cells BPH-1, derived from the benign prostatic hyperplasia, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) persistently activates the AhR signaling pathway and induces expression of xenobiotic metabolizing enzymes, such as CYP1A1 or CYP1B1. Here we demonstrate that TGF-β1 suppresses the AhR-mediated gene expression through multiple mechanisms, involving inhibition of AhR expression and down-regulation of nuclear AhR, via a SMAD4-dependent pathway. In contrast, TCDD-induced AhR signaling does not affect either TGF-β1-regulated gene expression or epithelial-to-mesenchymal transition. These observations suggest that, in the context of prostate epithelium, TGF-β1 signaling plays a dominant role in the crosstalk with AhR signaling pathway. Given the importance of TGF-β1 signaling in regulation of prostate epithelial tissue homeostasis, as well as the recently revealed role of AhR in prostate development and tumorigenesis, the above findings contribute to our understanding of the mechanisms underlying the crosstalk between the two signaling pathways in the prostate-specific context.
Keywords: Signal Transduction; Cells, Cultured; epitelové buňky; Humans; Transforming Growth Factor beta1; prostata; Receptors, Aryl Hydrocarbon; Prostate; signální transdukce; transformující růstový faktor beta1; mužské pohlaví; Ligands; Polychlorinated Dibenzodioxins; rekombinantní proteiny; ligandy; kultivované buňky; Epithelial Cells; Recombinant Proteins; lidé; polychlorované dibenzodioxiny; receptory aromatických uhlovodíků; Male